Die vroeg-Christelike doop as kultureelrituele simbool - Groenewald, J. (Koers, 2002)
Early Christian baptism as a cultural, ritual symbol This article describes baptism as a cultural, ritual symbol. Baptism is seen as a symbol consisting of reason, value and meaning. The reason why baptism functions as a symbol has a historical basis in the death and resurrection of Jesus. For the first Jesus followers the value of being baptized was that they became part of a new value system. This value system gave meaning to the lives of the baptized and others who stood in relationship with them. The initiation into this alternative lifestyle (through baptism) was made possible by an altered state of consciousness.